Uji Klinik: Efek Konsumsi Nata de cocolawak pada Kadar Glukosa Darah Wanita Sehat - Indah Solihah; Ina Suci Pratiwi; Miksusanti Miksusanti (Seminar Nasional Lahan Suboptimal, 2020)
Solihah I, Pratiwi IS, Miksusanti M.  2020. Uji Klinik: Efek Konsumsi Nata de cocolawak pada Kadar Glukosa Darah Wanita Sehat. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Temulawak (Curcuma xanthorrhiza Roxb.) has curcumin as an active compound. Curcumin is reported to have the effect for reducing blood glucose serum in an animal study. Nata de cocolawak is nata de coco dessert contain temulawak extract. Curcumin content on nata de cocolawak product was measured spectrophotometrically. The clinical experimental study design was done to evaluate the effect of consuming nata de cocolawak on blood glucose serum. Respondents were healthy women divided into two groups, group 1 who was consume nata de cocolawak and group 2 who was consume nata de coco, three times a day for 30th days. The yield results show that nata de cocolawak is contain 27,603% curcumin from temulawak dried rhizome. The respondent who was consume nata de cocolawak has lower blood glucose serum than the respondents who was consume nata de coco